Acute portal vein thrombosis secondary to COVID-19: a case report - Borazjani, Roham (BMC Gastroenterol, 2020)
BACKGROUND: COVID-19 pneumonia exhibits several extra-pulmonary complications. CASE PRESENTATION: A 23-year old, asthmatic male with coronavirus pneumonia developed with generalized, acute abdominal pain. Further evaluations revealed a mild ascites and portal vein thrombosis although the patient received proper anticoagulation therapy. Routine lab data regarding the secondary causes of portal vein thrombosis were normal. CONCLUSION: We speculated that the underlying cause of portal vein thrombosis in our case was coronaviruses. Therefore, clinicians should always consider thrombosis and other hypercoagulable diseases in patients with COVID-19.